Development of Interactive Video as Learning Media to Teach English Speaking Skills for High School Students - Khoirina, Vita; Makrifah, Istina Atul; Saifudin, Ahmad (IKIP Siliwangi, 2025)
This study aims to develop and evaluate an interactive video as a learning media to teach students' English-speaking skills. The research follows the Research and Development (R&D) with ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. In the analysis stage, classroom observations and student questionnaires were conducted to identify learning needs. Based on the findings, the design stage involved determining the appropriate interactive video content, creating scripts, and structuring the video. The development stage included video editing using CapCut, followed by expert validation. The results showed high validity scores: instrument validation (92.5%), media validation (87.5%), and material validation (92.5%), all categorized as